Early Adolescent Substance Use in Mexican Origin Families: Peer Selection, Peer Influence, and Parental Monitoring - Schofield, Thomas J. (Drug Alcohol Depend, 2015)
BACKGROUND: Because adolescents vary in their susceptibility to peer influence, the current study addresses potential reciprocal effects between associating with deviant peers and use of alcohol, tobacco and other drugs (ATOD), as well as the potential buffering role of parental monitoring on these reciprocal effects. METHOD: 674 children of Mexican origin reported at fifth and seventh grade(10.4 years old at fifth grade)on the degree to which they associated with deviant peers, intended to use alcohol, tobacco or other drugs (ATOD) in the future, and had used controlled substances during the past year. Trained observers rated parental monitoring from video-recorded family interactions at the first assessment. RESULTS: Youth who intended to use ATODs during fifth grade experienced a relative increase in number of deviant peers by seventh grade, and youth with more deviant peers in fifth grade were more likely to use ATODs by seventh grade. Parental monitoring buffered (i.e., moderated) the reciprocal association between involvement with deviant peers and both intent to use ATODs and actual use of ATODs. CONCLUSIONS: Parental monitoring can disrupt the reciprocal associations between deviant peers and ATOD use during the transition from childhood to adolescence